Ethics in the Philosophy of William James (Comprehensive Journal of Science, 2026)
The contemporary view of ethics has not escaped the influence of science. As a result of the dominance of science in all areas of social, natural, and psychological life, the idea of relativism became increasingly widespread until it cast its shadow over moral values in particular. According to William James, ethics cannot be built upon scientific knowledge of objective truth. Rather, what matters is the will to affirm those moral beliefs that prove to be beneficial. If such beliefs fulfill their function, then they are considered true. However, what is beneficial for one group of people may not be beneficial for another group. Likewise, if we judge the value of ideas by the extent to which they can be transformed into actions that reshape and reconstruct the world, we find that people have different interests and therefore are often bound to judge their value differently.